Neurotransmitter metabolites in CSF: an external quality control scheme - Bräutigam, Christa; Weykamp, C.; Hoffmann, Georg F.; Wevers, R. A. (Journal of inherited metabolic disease, 2002)
We report an international external quality control scheme on neurotransmitter metabolites in cerebrospinal fluid (CSF). The neurotransmitter metabolites homovanillic acid (HVA), 5-hydroxyindoleacetic acid (5-HIAA) and 3-methoxy-4-hydroxyphenylglycol (MHPG) are analysed to diagnose inborn errors of neurotransmitter metabolism. HVA is the catabolite of dopamine; 5-HIAA is the catabolite of serotonin; and MHPG is the catabolite of noradrenaline. In the first phase, 12 laboratories from six countries participated in this special quality control scheme to define the present state of the art and achieve harmonization in analytical outcome and interpretation. In the second part, recoveries, dilutions and methods for sample preparation were compared. The results of 3 of 12 laboratories were excluded because of unacceptable intralaboratory coefficients of variations (CV) for HVA and/or 5-HIAA. The inter- and intralaboratory CVs, the linearity and the recovery were acceptable for the other laboratories for both parameters.Unacceptable differences in the reference ranges between laboratories, leading to differences in interpretation of the results, became obvious. There was a significant improvement of the interlaboratory CV for HVA after standardization with a calibrator. The reproducibility of MHPG measurement appeared to be adequately established in only two laboratories and recovery was low in all five measuring this metabolite. The quality control scheme is an invaluable tool for controlling the analytical outcome and providing support to laboratories to improve their quality.